2009
DOI: 10.1089/jmf.2008.0081
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacity and Polyphenolic Content of Blueberry (Vaccinium corymbosumL.) Leaf Infusions

Abstract: Antioxidant capacity and polyphenolic content of leaf infusions prepared from six highbush blueberry cultivars (Vaccinium corymbosum L.), one wild lowbush blueberry cultivar (Vaccinium myrtillus L.), and one commercially available mix of genotypes were determined. In order to simulate household tea preparation conditions, infusions were prepared in water heated to 95 degrees C. The dynamics of extraction of polyphenolic antioxidants were monitored over the course of 30 minutes. Extraction efficiency, quantifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 27 publications
4
37
0
Order By: Relevance
“…[21][22][23] Infusions of BBL have been used as a folk medicine treatment for lifestyle-related diseases, 8,9) and recent reports have revealed that the polyphenolic content and anthocyanidin from BBL had several physiological functions. 24,25) Taken together, these findings led us to explore the effects of hot water extraction and the polyphenolic extracts from BBL on the lipid metabolism in OLETF rats.…”
Section: )mentioning
confidence: 99%
“…[21][22][23] Infusions of BBL have been used as a folk medicine treatment for lifestyle-related diseases, 8,9) and recent reports have revealed that the polyphenolic content and anthocyanidin from BBL had several physiological functions. 24,25) Taken together, these findings led us to explore the effects of hot water extraction and the polyphenolic extracts from BBL on the lipid metabolism in OLETF rats.…”
Section: )mentioning
confidence: 99%
“…An increase in TPC may be attributed to transformation of proanthocyanidins (oligomeric and polymeric flavan-3-ols) to dimers or monomeric phenolic compounds or formation of other phenolic compounds during juice storage (Piljac-Zegarac et al, 2009). The trend of evolution of TPC during storage is also dependent on fruit species besides processing and preservation conditions employed.…”
Section: (-)-mentioning
confidence: 99%
“…According to all four assays, bark extract has shown a significantly lower antioxidant capacity in comparison to the leaf extract (2.6- 33 and explained by the fact that ABTS •+ radical reacts with a wider range of compounds, including both hydrophilic and lipophilic antioxidants. 34 Furthermore, the ORAC value of R. intermedia methanol extracts (leaf: 738.27 ± 58.58 µmol TE g -1 DW , bark: 117.65 ± 14.43 µmol TE g -1 DW) was greater than the antioxidant capacity measured either by ABTS or DPPH assay (3.4, and 3.7-fold, respectively, for leaf and 1.6 and 2.04-fold, respectively, for bark extracts).…”
Section: Antioxidant Capacitymentioning
confidence: 91%